Charge transport in organic nanocrystal diodes based on rolled-up robust nanomembrane contacts - Bandari, Vineeth Kumar; Varadharajan, Lakshmi; Xu, Longqian; Jalil, Abdur Rehman; Devarajulu, Mirunalini; Siles, Pablo F.; Zhu, Feng; Schmidt, Oliver G. (Beilstein Journal of Nanotechnology, 2017)
The investigation of charge transport in organic nanocrystals is essential to understand nanoscale physical properties of organic systems and the development of novel organic nanodevices. In this work, we fabricate organic nanocrystal diodes contacted by rolled-up robust nanomembranes. The organic nanocrystals consist of vanadyl phthalocyanine and copper hexadecafluorophthalocyanine heterojunctions. The temperature dependent charge transport through organic nanocrystals was investigated to reveal the transport properties of ohmic and space-charge-limited current under different conditions, for instance, temperature and bias.
Keywords: charge transport; nanomembrane; organic diode; organic nanocrystal; rolled-up nanotechnology